Preparation, characterizations and biological evaluations of new copper(II) complexes containing ONO pincer type ligands. (20th April 2018) - Elamathi, C.; Butcher, Ray; Prabhakaran, R.
Abstract : A new heterocyclic Schiff bases, 6‐methyl/8methyl‐2‐oxo‐1, 2‐dihydroquinoline‐3‐carboxaldehyde semicarbazones (H2 ‐6MOQsc‐H) (H 2 L 1 ) and (H2 ‐8MOQsc‐H) (H 2 L 2 ) and their corresponding copper(II) complexes [CuCl2 (H2 ‐6MOQsc‐H)].3H2 O (1 ), [CuCl2 (H2 ‐8MOQsc‐H)].3H2 O (2 ), [CuNO3 (H2 ‐6MOQsc‐H)(H2 O)].NO3 (3 ) and [CuNO3 (H2 ‐8MOQsc‐H)(H2 O)].NO3 (4 ) have been synthesized and characterized by various physicochemical techniques. The single crystal X‐ray diffraction and spectral data revealed that all of the complexes (1‐4 ), the ligands coordinated to the Cu(II) ion in a neutral manner via ONO donor atoms and all the complexes exhibited distorted squarepyramidal geometry. The consequence of electronegativity and ring size of nitrogen heterocyclic moiety of ONO donor type of copper(II) chelates on nucleic acid interaction and albumin binding was investigated by in vitro experiments. The interaction of compounds with calf‐thymus DNA (CT‐DNA) has been explored by absorption and emission titration, which exposed those ligands/complexes, could bind with CT‐DNA through electrostatic interaction. The results of gel electrophoresis proved the ability of complexes (1‐4 ) to cleave the pBR322 plasmid DNA. The interaction of serum albumin (BSA) was investigated by UV‐Vis, fluorescence, synchronous and three dimensional fluorescence spectra. In addition, radical scavenging activity, antifungal activity and cytotoxicity of the newly synthesized compounds were also evaluated. From the results of in vitro studies, it is seen that complex 3 has more potential as compared with other complexes and ligands. Abstract : The presented work focuses on the synthesis and biological evaluation of heterocyclic Schiff bases and their copper(II) metallates.